Estimation of growth rate, biosilica, protein and lipid content in locally isolated Fragellaria vaucheria - Yosef J. Ismaeel Al-Shahrii (College of Education for Pure Sciences, 2008)
Abstract The study was conducted in Mosul city, northern Iraq to obtain a local isolate of the algal, Fragellaria vaucheria (Bacillariophycophyta) . Maximum biomass (58 mg/l) was obtained after seven days of incubation. The ratio of precipitated biosilica in the cellular walls ranged between 30 to 35 % of the dry weight of the biomass. The amount of biosilica increased with progress of incubation period. The infra red spectrum test showed the high purity of isolated silica. The protein content increased with increase of algal growth and reached 125 mg/l after fifteenth days of incubation, Maximum lipid content (198 mg/l) was obtained after eleven days of incubation. Generally final pH value was higher than the initial one. The algal Fragellaria vaucheria have a wide pH range and the optimum pH for growth was 7.6 .